Cascade Reactions in Nanozymes: Spatially Separated Active Sites inside Ag-Core−Porous-Cu-Shell Nanoparticles for Multistep Carbon Dioxide Reduction to Higher Organic Molecules - O’Mara, Peter B.; Wilde, Patrick; Benedetti, Tania M.; Andrones, Corina; Cheong, Soshan; Gooding, Justin; Tilley, Richard D.; Schuhmann, Wolfgang (Journal of the American Chemical Society, 2019)
Enzymes can perform complex multistep cascade reactions by linking multiple distinct catalytic sites via substrate channeling. We mimic this feature in a generalized approach with an electrocatalytic nanoparticle for the carbon dioxide reduction reaction comprising a Ag core surrounded by a porous Cu shell, providing different active sites in nanoconfined volumes. The architecture of the nanozyme provides the basis for a cascade reaction, which promotes C−C coupling reactions. The first step occurs on the Ag core, and the subsequent steps on the porous copper shell, where a sufficiently high CO concentration due to the nanoconfinement facilitates C−C bond formation. The architecture yields the formation of n-propanol and propionaldehyde at potentials as low as −0.6 V vs RHE.
Keywords: Cascade Reactions; Nanozymes; Ag-Core−Porous-Cu-Shell Nanoparticles; Carbon Dioxide; Organic Molecules